Formulation Approaches to Crystalline Status Modification for Carotenoids: Impacts on Dissolution, Stability, Bioavailability, and Bioactivities - Wan-Yi Liu; Yun-Shan Hsieh; Horng-Huey Ko; Yu-Tse Wu (MDPI AG, 2023)
Carotenoids, including carotenes and xanthophylls, have been identified as bioactive ingredients in foods and are considered to possess health-promoting effects. From a biopharmaceutical perspective, several physicochemical characteristics, such as scanty water solubility, restricted dissolution, and susceptibility to oxidation may influence their oral bioavailability and eventually, their effectiveness. In this review, we have summarized various formulation approaches that deal with the modification of crystalline status for carotenoids, which may improve their physicochemical properties, oral absorption, and biological effects. The mechanisms involving crystalline alteration and the typical methods for examining crystalline states in the pharmaceutical field have been included, and representative formulation approaches are introduced to unriddle the mechanisms and effects more clearly.